Figuring rural development concepts and cases of land use, sustainability and integrative indicators - Hobbes, Marieke 1976-; IG Publishing ([Leiden] Leiden University Press, 2010)
This research, with empirical data from the Philippines, Vietnam, India, and Laos, represents a merger of environmental science and rural development economics. It develops a unique measuring rod of wealth and poverty: Freely Disposable Time, which integrates time and cash flow of households to quantify concepts of freedom and development capacity.
"geboren te Zoeterwoude in 1976"
Thesis (Ph. D.)--Universiteit Leiden, 2010.
Electronic reproduction.
Keywords: Rural development -- Planning -- Research; Rural development -- Southeast Asia; Electronic books; Southeast Asia -- Environmental conditions; Southeast Asia -- Economic conditions